2013
DOI: 10.4161/rna.23764
|View full text |Cite
|
Sign up to set email alerts
|

Protospacer recognition motifs

Abstract: Protospacer adjacent motifs (PAMs) were originally characterized for CRISPR-Cas systems that were classified on the basis of their CRISPR repeat sequences. A few short 2–5 bp sequences were identified adjacent to one end of the protospacers. Experimental and bioinformatical results linked the motif to the excision of protospacers and their insertion into CRISPR loci. Subsequently, evidence accumulated from different virus- and plasmid-targeting assays, suggesting that these motifs were also recognized during D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
177
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(183 citation statements)
references
References 68 publications
6
177
0
Order By: Relevance
“…Within this overall theme, three CRISPRCas system types (I, II, and III) use distinct molecular mechanisms to achieve nucleic acid recognition and cleavage (54,55). The protospacer adjacent motif (PAM), a short sequence motif adjacent to the crRNA-targeted sequence on the invading DNA, plays an essential role in the stages of adaptation and interference in type I and type II systems (39,(56)(57)(58). The type I and type III systems use a large complex of Cas proteins for crRNA-guided targeting (47,(59)(60)(61)(62)(63).…”
Section: History and Biology Of Crispr-cas Systemsmentioning
confidence: 99%
“…Within this overall theme, three CRISPRCas system types (I, II, and III) use distinct molecular mechanisms to achieve nucleic acid recognition and cleavage (54,55). The protospacer adjacent motif (PAM), a short sequence motif adjacent to the crRNA-targeted sequence on the invading DNA, plays an essential role in the stages of adaptation and interference in type I and type II systems (39,(56)(57)(58). The type I and type III systems use a large complex of Cas proteins for crRNA-guided targeting (47,(59)(60)(61)(62)(63).…”
Section: History and Biology Of Crispr-cas Systemsmentioning
confidence: 99%
“…In addition to facilitating self versus non-self discrimination by Cas9 (Shah et al, 2013), because direct repeats do not contain PAM sites, biochemical and structural characterization of SpCas9 suggested that PAM recognition is involved in triggering the transition between Cas9 target binding and cleavage conformations (Sternberg et al, 2014; Jinek et al, 2014; Nishimasu et al, 2014). …”
Section: Protospacer Adjacent Motif: Cas9 Target Range and Search Mecmentioning
confidence: 99%
“…A recent study reported functional synergy between an R–M system and CRISPR–Cas in Streptococcus thermophilus 21 , which suggests that fragments of invader DNA that are generated by the R–M system might be potential substrates for spacer acquisition. The CRISPR–Cas system selects suitable spacers by the detection of a specific protospacer adjacent motif (PAM) 2224 (BOX 1), followed by processing of the DNA substrates into spacer precursors of a defined size 25 . After the opening of the leader-end repeat by the nicking of both strands at opposite sides of the repeat 26 , the new spacer is integrated in a specific, PAM-dependent orientation 25,27 (FIG.…”
Section: Acquisition Of Spacersmentioning
confidence: 99%
“…Instead, in silico analyses of sequences that flank the protospacers recognized by CRISPR–Cas type I and type II systems have revealed that type-specific short sequences (of 2–3 nucleotides), which are collectively known as protospacer adjacent motifs (PAMs) 22,23 , are necessary for discrimination. The most important feature of the PAM is that it differs from the corresponding sequence of the CRISPR repeat 24 , which enables discrimination between a non-self target and a self non-target. Indeed, experimental analyses of CRISPR interference by type I (REFS 54,99,101,103) and type II (REFS 76,77) systems have confirmed an important role for the PAM motif.…”
Section: Figurementioning
confidence: 99%